PERTUMBUHAN DAN HASIL TANAMAN BAWANG MERAH (Allium ascalonium L.) PADA UJI PUPUK GUANO DI TANAH SAWAH RENON - Grace Maharani Putri; I Made Suryana; Bagus Putu Udiyana; I Putu Sujana (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2022)
The research is entitled "Growth and Yield of Shallots (Allium ascalonium L.) Using Guano Fertilizer Test in Renon Rice Fields". The study aims to determine the effect of the dose of guano fertilizer on the development of shallot plants. The research was conducted in Renon Village, South Denpasar District. The study used a Randomized Block Design (RAK) method with the treatments studied: dosage of guano fertilizer (G), which include Go: without guano fertilizer, G1: 3 ton/acre (90 g/10 kg of soil), G2: 6 ton/acre (180 g/10 kg of soil), G3 : 9 ton/acre (270 g/10 kg of soil), G4 : 12 ton/acre (360 g/10 kg of soil), G5 : 15 ton/acre (450 g/10 kg of soil). Each treatment was repeated for 4 times to obtain 24 treatments. The result showed that guano fertilizer had a very significant effect on the parameters of plant height, number of leaves, number of tillers and number of bulbs, total plants gross weight, total dry mass of plants, gross weight of bulb on shallot, air dried mass of bulb, oven net weight of bulb. The application of organik guano fertilizer 12 ton/acre (360 g/10 kg soil) shows best results on the growth and yield of shallots with the yield of fresh mass of shallot bulb was 34.91 g, air dried mass of bulb was 33.86 g, and oven dry mass of bulb was 31.62 g